Linguocultural function of taboo in cognition of nation - Kashkeyeva, A.B.; Kulzhanova, B.R. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2023)
The concept of "taboo" is one of the basic concepts in the linguistic picture of the world and is of great importance both for an individual linguistic personality and for the linguistic community as a whole. Taboo means "sacred" or "untouchable" in Tongan and comes from superstitions and various fears. This is a ban not only on the concept, but also on the name of this concept in the language, that is, on the word. Since knowledge in general can be defined as a socially and historically formed human attitude to the world, the study examines the linguistic and cultural features of prohibitions and taboos arising from folk knowledge. The main goal is to focus on the problem of taboos in consciousness, to compare the worldview and understanding of the ban by Kazakhs, to determine the linguistic, linguistic, cultural, educational values of taboos based on the continuity of knowledge and traditions. As a result of the research, it was proved that the phenomenon is viable and it needs to be studied from both an ethnographic and linguistic point of view. The differences between taboos and euphemisms are shown. Functional-semantic, cognitive models of analysis in this study can be used in the field of lexicology.